Localized wind model of Weibull distribution in Vung Tau, Vietnam - Tran, Van Chung; Nguyen, Minh Giam; Ho, Dinh Duan; Nguyen, Van Hung; Nguyen, Huu Huan; Phan, Minh Thu (Vietnam Journal of Marine Science and Technology, 2025)
The wind data set of 10 m on the sea surface is provided by Vung Tau Meteorological Station for 2011–2022, with a frequency of 6 h. The purpose of this paper is to find the most effective parameters, that are scale parameter ‘c’ and shape parameter ‘k’ for the Weibull distribution for the wind regime in Vung Tau based on analyzing and comparing the efficiency of ten numerical methods, namely, the empirical method of Justus (EMJ), the empirical method of Lysen (EML), the method of moments (MoM), the graphical method (GM), the Mabchour’s method (MMab), the energy pattern factor method (EPFM), the maximum likelihood method (MLM), the modified maximum likelihood method (MMLM), the equivalent energy method (EEM), and the alternative maximum likelihood method (AMLM). According to the analysis results, the MLM method is best suited for the wind regimes from February to December; MLM and EMJ methods is best suited for January wind regimes; The AMLM, MLM, and EML methods are best suited for the wind regime in December the MLM and EMJ methods are best suited for November. The MMab method could result in inaccurate forecasting of the wind regime in the Vung Tau area.